Ultrasonography and 3D-CT Follow-Up of Extrahepatic Portal Vein Aneurysm: A Case Report - Norio Yukawa; Makoto Takahashi; Kazuyoshi Sasaki; Takuma Mori; Ayumi Matsuo; Kuniyasu Ito; Hiroyuki Kirikoshi; Kiyoshi Ohya; Nobuyuki Wada; Yasushi Rino; Munetaka Masuda (Case Reports in Medicine)
Extrahepatic portal vein aneurysm is a rare disorder. From 1956 to 2008, we found only 43 published English-language reports, including 67 cases, using Pub Med. We report a case of a 77-year-old woman who had complaints of lower abdominal fullness and residual urine. We performed ultrasonography (US), which demonstrated a congenital extrahepatic portal vein aneurysm. She had no obvious symptoms of the extrahepatic portal vein aneurysm. She had undergone gastrectomy without blood transfusion for gastric ulcer more than 20 years ago. Physical examination revealed no abnormal findings. US revealed a 2.2×1.8 cm, round shaped hypoechogenic lesion at the hepatic hilum. Color Doppler US showed bidirectional colors due to circular flow within this lesion. 3D-CT and CT angiography demonstrated that the saccular aneurysm at the hepatic hilum was 3.0 cm in diameter and was enhanced equal to that of portal vein.Twenty-six months after the diagnosis, the aneurysm had not grown in size. Since our patient had no serious complaints or liver disease, surgical procedures had not been employed. US and 3D-CT are noninvasive diagnostic techniques and are helpful in the diagnosis and follow-up of extrahepatic portal vein aneurysms.